Essential oils from Eucalyptus species: a review of their activities, applications, and the Brazilian market - Mayara Rodrigues; Paulo Mazzafera (Acta Botânica Brasílica, 2025)
Abstract Essential oils are volatile, lipophilic substances mainly composed of terpenes, derived from secondary metabolism. Widely used in pharmaceutical, agricultural, and cosmetic industries, essential oils from eucalyptus species are particularly notable for their economic and biological significance. This review explores the antimicrobial, anti-inflammatory, antioxidant, antiviral, and insecticidal activities of essential oils from various eucalyptus species and their isolated constituents, such as eucalyptol and α-terpineol. Because eucalyptus represents 96.7% of the reforested area in Brazil, economic analyses focused on the Brazilian market, highlighting a 25-year trajectory of production and trade, the dominance of eucalyptol-rich oils, and the growing demand for sustainable and high-quality products. Future market prospects include expanding the use of underutilized species, improving oil formulations for enhanced stability and bioavailability, and meeting stringent international quality standards. Addressing these challenges and opportunities underscores the essential role of ongoing research in leveraging eucalyptus essential oils as versatile and sustainable bioresources.